Emotional Understanding in Children with A Cochlear Implant. (6th October 2018) - Wang, Huizhi; Wang, Yifang; Hu, Yousong
Abstract: Emotional understanding plays an important role in the physical and mental health of children. To determine whether the development of emotional understanding is delayed in children with a cochlear implant (CI), 30 children with a CI and 30 matched children with typical hearing aged between 3 and 9 years old completed three tasks (facial expression, tone expression and scene of emotion matching), in which they identified four basic emotions (happiness, sadness, anger, and fear). The participants included 40 preschool children and 20 school-aged children. Compared with the children with typical hearing, the children with a CI were significantly delayed in the ability to understand emotion; the tone expression matching task was the most difficult task for all participants; and the school-aged children performed better than the preschool children, but this trend was only observed in the typical hearing group; and happiness was the easiest emotion to identify.